Rethinking Employee Retention: Psychological Determinants That Matter Most - Febriyanti, Andini; Riadi, Refren; Surtinah, Wiwin (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2026)
Employee retention remains a critical challenge for organizations, particularly in identifying psychological factors that influence employees’ decisions to stay. While prior research highlights job satisfaction and self-efficacy as key predictors, findings remain inconsistent regarding their relative impact on retention. This study examines the effects of job satisfaction and self-efficacy on employee retention and identifies the more dominant factor. Using a quantitative approach, data were collected from 50 respondents through questionnaires with proportional stratified random sampling. Analysis was conducted using SPSS version 21, including partial (t-test) and simultaneous (F-test) tests. Results show that job satisfaction has a positive and significant effect on employee retention (t = 4.987 > 1.677; p < 0.05), while self-efficacy has no significant effect (t = -0.024 < 1.677; p > 0.05). However, both variables simultaneously influence retention significantly (F = 21.212 > 3.195; p < 0.05). These findings indicate that job satisfaction is the primary determinant of employee retention. This study contributes by clarifying the inconsistent role of self-efficacy and emphasizing the importance of enhancing job satisfaction to improve retention outcomes.